Meningkatkan Kosakata dan Pemahaman Membaca melalui Kesadaran Morfologis pada Pembelajar Bahasa Inggris sebagai Bahasa Asing (EFL) - Tewarat, Sipri Hanus; Afriana, Afriana (eScience Humanity Journal, 2025)
Reading comprehension remains one of the biggest issues with second language (L2) learners, particularly due to a lack of vocabulary knowledge. This study addresses the role of morphological instructional methods to enhance students' vocabulary acquisition, particularly prefixes and suffixes via reading activities. Drawing on a literature review method, the research combines outcomes from a number of studies to identify effective morphological approaches that make it easy for English as a Foreign Language (EFL) learners. It focuses on how morphological awareness—understanding word structure and formation—is capable of improving vocabulary comprehension and subsequently reading comprehension. The study also examines the role of inflectional and derivational morphemes in instructional settings, highlighting their ability to facilitate students to make inferences about word meaning, increase vocabulary, and produce greater levels of literacy. Results reveal that the integration of morphological strategies into instruction in the classroom not only enhances students’ language proficiency but also enhances reading motivation and engagement. The research concludes by recommending that English language educators incorporate explicit morphological instruction to support learners in decoding and constructing words effectively